Pulse Dosing of 10-kHz Paresthesia-Independent Spinal Cord Stimulation Provides the Same Efficacy with Substantial Reduction of Device Recharge Time. Issue 1 (2nd October 2021) - Provenzano, David; Tate, Jordan; Gupta, Mayank; Yu, Cong; Verrills, Paul; Guirguis, Maged; Harrison, Nathan; Smith, Thomas; Azalde, Rose; Bradley, Kerry
Abstract: Objective: This study was designed to assess whether using pulse dosing (PD) (regularly cycled intermittent stimulation) of high-frequency 10-kHz spinal cord stimulation (10-kHz SCS) can reduce device recharge time while maintaining efficacy in patients with chronic intractable back pain with or without leg pain. Design: Prospective, multicenter, observational study. Methods: Patients successfully using 10-kHz SCS at 100%ON (i.e., continuously with no PD) for >3 months were consecutively enrolled. After a 1-week baseline period of documenting their pain twice daily on a 0–10 numerical rating scale (NRS) using 100%ON of their "favorite" program, all subjects were reprogrammed to 14%PD for 10–14 days. If subjects preferred 14%PD to 100%ON, they were programmed to 3%PD; otherwise, they were programmed to 50%PD. Subjects used this next program for another 10–14 days. Subjects then entered a 3-month observational period during which they were requested to use but not limited to their most preferred %PD program. Toward the end of 3 months, subjects completed a 7-day NRS diary and indicated a final %PD program preference. Study endpoints included %PD preference, mean diary NRS by %PD, and daily minutes and patterns of charging. Results: Of 31 subjects completing the study, 81% preferred less than 100%ON. Among the subjects, 39% preferred 3%PD, 32% preferred 14%PD, 10% preferred 50%PD, and 19% preferred 100%ON. Average daily charge durations were 8.3 ± 3.1 minutes for 3%PD, 13.9 ± 4.9 minutes for 14%PD, 26.2 ± 7.4 minutes for 50%PD, and 43.8 ± 10.9 minutes for 100%ON. Regression modeling suggested that pain relief was weighted as more than twice as influential as charging in preference for reduced %PD. Conclusions: This prospective study suggests that 10-kHz SCS therapy with PD may be successfully used in a large majority of 10-kHz SCS responders, maintaining efficacy while reducing device charging time by nearly two thirds.